2018
DOI: 10.1039/c7cp06042d
|View full text |Cite
|
Sign up to set email alerts
|

The effects of glycine, TMAO and osmolyte mixtures on the pressure dependent enzymatic activity of α-chymotrypsin

Abstract: High pressure is an important feature of certain natural environments, such as the deep sea where pressures up to about 1000 bar are encountered. Further, pressure effects on biosystems are of increasing interest for biotechnological applications, such as baroenzymology. We studied the effect of two different natural osmolyte mixtures, with major components being glycine and trimethylamine-N-oxide (TMAO), on the activity of α-chymotrypsin, using high-pressure stopped-flow methodology in combination with fast U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 56 publications
3
25
0
Order By: Relevance
“…This nicely demonstrates the power of the method in determining accurate volume changes. Such small ΔV ‐values of α‐CT‐catalyzed hydrolysis reactions are in good agreement with literature results for this and other substrates in pure buffer solution [38–40] . The similar ΔV ‐values for the various solution conditions imply minor, if at all, differences in the transition state complex, i. e. the structure of the reaction center itself.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This nicely demonstrates the power of the method in determining accurate volume changes. Such small ΔV ‐values of α‐CT‐catalyzed hydrolysis reactions are in good agreement with literature results for this and other substrates in pure buffer solution [38–40] . The similar ΔV ‐values for the various solution conditions imply minor, if at all, differences in the transition state complex, i. e. the structure of the reaction center itself.…”
Section: Resultssupporting
confidence: 91%
“…We have selected the hydrolysis of the substrate N ‐succinyl‐Ala‐Ala‐Pro‐Phe‐ p ‐nitroanilide (SAAPP p NA) by α‐CT, forming the products N ‐succinyl‐Ala‐Ala‐Pro‐Phe and p ‐nitroanilide (which can be detected by time‐lapse absorption spectroscopy), as a model reaction system in the pressure range from ambient pressure up to 2 kbar. The effect of the pure cosolvents on the activity of the enzyme has been reported [39,40] . The focus of this work was mainly on the influence of the crowding agents PEG and dextran on the reaction, and to explore if the combined effects of pressure, cosolvents and crowding agents are additive, synergistic or antagonistic, and if this set of parameters can be used to optimize the activity of the enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…( 2 ) (see below). All Δ V ≠ values exhibit a negative value (order of magnitude, −8… −11 cm 3 mol −1 ), which is similar to that described in the literature 19 , 20 . Furthermore, the Δ V ≠ slightly increases with increasing substrate concentration (Table SI 3 ), reaching plateau values for substrate concentrations of about 2 mM, i.e., for concentrations where the enzyme is saturated with substrate.…”
Section: Resultssupporting
confidence: 88%
“…The study indicated the high-pressure effects on different biochemical systems where a particular focal point was laid on the effects of pressure on osmolytes such as TMAO, urea, ectoine, glycerol, and glycine as well as the dipeptides acetyl-N-methylglycine amide, acetyl-N-methylalanine amide, and acetyl-N-methyl leucine amide. [19,20]. The study also reported the ability of osmolytes like polyethylene glycol and TMAO for inhibiting of the depolymerization of individual microtubule filaments and that they may potentially play an essential role in in vivo microtubule dynamics [21].…”
Section: Mechanisms Of Actions Of Osmolytesmentioning
confidence: 90%